Intervenciones Asistidas Por Animales: Intervenciones Con Perros En Adultos Mayores A Partir Del Enfoque Multimodal - Olarte, MarÃa Alejandra; Videla, Marcos DÃaz (European Scientific Journal, ESJ, 2016)
Animal Assisted Interventions has been used as a complementary therapy for little longer than fifty years. Scientific publications about empiric investigations that have employed dogs in therapeutic work, mainly with senior citizens, are reviewed. LazarusÂ´s Multimodal Model is taken as a guide. Based on this model, assisted interventions with dogs that can result potentially beneficial to this population, are proposed. The relevance of the Multimodal approach for the design of interventions and therapeutic programs is highlighted.